English as a second language for Cambridge IGCSERG : Workbook - Akhurst, Chris; Bowley, Lucy (Oxford : Oxford University Press, 2014)
Supporting the Complete English as a Second Language for Cambridge IGCSE Student Book, and fully matched to the Cambridge IGCSE syllabus, this Workbook builds fluency and exam confidence. It provides rigorous practice in key skill areas, through varied and relevant activities that keepstudents engaged. Extra digital content gives students vital listening practice, preparing learners for complex tasks like "listening for inference".